2022
DOI: 10.1021/acs.chemmater.2c01178
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Domain Engineering Using Structural Defect Ordering

Abstract: Ferroelectrics have become indispensable in the development of energyefficient oxide electronics. Their domain state is closely linked to the final device functionality, making domain engineering in technology-compatible thin films of paramount importance. Here we demonstrate the local control of domain formation in two-dimensional epitaxial ferroelectric films using structural defect engineering through the substrate topography. Using a combination of first-principles calculations, atom probe tomography, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 57 publications
(97 reference statements)
0
10
0
Order By: Relevance
“…The achievement of high-quality, twin-free films enabled the investigation of domain engineering in the Aurivillius materials. The first studies indicated the ability to control the formation of structural defects in the layered structure of the films using substrate morphology; see Figure d–g . The ordering of the so-called steric out-of-phase boundaries appears as key in the controlled formation of in-plane-polarized ferroelectric domains.…”
Section: Robust and Deterministic Ferroelectric Behavior In The Ultra...mentioning
confidence: 99%
See 4 more Smart Citations
“…The achievement of high-quality, twin-free films enabled the investigation of domain engineering in the Aurivillius materials. The first studies indicated the ability to control the formation of structural defects in the layered structure of the films using substrate morphology; see Figure d–g . The ordering of the so-called steric out-of-phase boundaries appears as key in the controlled formation of in-plane-polarized ferroelectric domains.…”
Section: Robust and Deterministic Ferroelectric Behavior In The Ultra...mentioning
confidence: 99%
“…(h, i) Isosurfaces around an out-of-phase boundary in the Bi 5 FeTi 3 O 15 film containing a high Bi density. Panels d–i reproduced with permission from ref . Copyright 2022 by the American Chemical Society.…”
Section: Ferroelectricity In the Ultrathin Regime: Advanced Character...mentioning
confidence: 99%
See 3 more Smart Citations